Software Architecture Evaluation Using Architecture Tradeoff Analysis Method (ATAM): A Case Study of UUM Learning Zone System - Haruna, Mohammed Zaharadden (2010)
Software architecture evaluation has been employed by many organizations around the world to be the required standard procedure in the development of software system. It has widely gained general acceptance from both company and the research community because of its immense contributions. The UUM learning zone had only been operating for just a semester and has never been evaluated before. This study extends the use of Architecture Tradeoff Analysis Method (ATAM) a scenario-based evaluation method to evaluate the software architecture of learning zone which is the Universiti Utara Malaysia's learning management system used for online education within the university community. The findings relatively showed that they were no risk and tradeoff in the architecture and some sensitivity point were identified.